Forced Migration, Staying Minorities, and New Societies: Evidence from Post-War Czechoslovakia - Jakub Grossmann; Štepán Jurajda; Felix Roesel (Institute of Labor Economics (IZA), 2021)
How do staying minorities that evade ethnic cleansing integrate into re-settled communities? After World War Two, three million ethnic Germans were expelled from Czechoslovakia's Sudetenland, but some were allowed to stay, many of them left-leaning anti-fascists. We study quasi-experimental local variation in the number of anti-fascist Germans staying in post-war Czechoslovakia and find a long-lasting footprint: Communist party support, party cell frequencies, far-left values, and social policies are stronger today where anti-fascist Germans stayed in larger numbers. Our findings also suggest that political identity supplanted German ethnic identity among stayers who faced new local ethnic majorities.
Keywords: J15; F22; D72; D74; N34; 330; forced migration; displacement; ethnic cleansing; stayers; minorities; identity; integration; communist party; Czechoslovakia; Sudetenland